2009
DOI: 10.1677/erc-09-0104
|View full text |Cite
|
Sign up to set email alerts
|

Phase III trial of chemotherapy using 5-fluorouracil and streptozotocin compared with interferon α for advanced carcinoid tumors: FNCLCC–FFCD 9710

Abstract: The aim of this randomized multicenter phase III trial was to compare chemotherapy and interferon (IFN) in patients with metastatic carcinoid tumors. Patients with documented progressive, unresectable, metastatic carcinoid tumors were randomized between 5-fluorouracil plus streptozotocin (day 1-5) and recombinant IFN-a-2a (3 MU!3 per week). Primary endpoint was progression-free survival (PFS). From February 1998 to June 2004, 64 patients were included. The two arms were well matched for median age, sex ratio, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 21 publications
0
54
0
5
Order By: Relevance
“…However, it later proved ineffectual in this and several other randomized phase III studies (Dahan et al, 2009;Hagan et al, 2013;Klingbiel et al, 2015;Saltz et al, 2007;Taieb et al, 2014). Therefore, irinotecan is not used in the adjuvant setting in CRC patients.…”
Section: Msi As a Prognostic Marker With Adjuvant 5-fu And Irinotecanmentioning
confidence: 90%
“…However, it later proved ineffectual in this and several other randomized phase III studies (Dahan et al, 2009;Hagan et al, 2013;Klingbiel et al, 2015;Saltz et al, 2007;Taieb et al, 2014). Therefore, irinotecan is not used in the adjuvant setting in CRC patients.…”
Section: Msi As a Prognostic Marker With Adjuvant 5-fu And Irinotecanmentioning
confidence: 90%
“…Their antiproliferative efficacy, however, is limited and rarely associated with objective tumor remissions (8-11%). Nevertheless, these drugs have a value in tumor growth stabilization and prolongation of time to tumor progression (Dahan et al 2009, Rinke et al 2009, Modlin et al 2010c. Although there is no regulatory approval for antiproliferative indications in all GEP-NENs (except for midgut NENs), SSAs especially are frequently used as first-line therapy in G1/G2 NENs.…”
Section: The Current Status Of Medical Therapy In Gep-nensmentioning
confidence: 99%
“…Although systemic chemotherapy can be of value in some PNENs, the vast majority of midgut NENs are slow proliferating and are nonresponsive to cytotoxic drugs (Sun et al 2005, Dahan et al 2009). Data supporting the use of streptozotocin-based chemotherapy either with 5-FU and/or doxorubicin mainly come from older studies using a variety of nonstandard endpoints (Moertel et al 1992).…”
Section: The Current Status Of Medical Therapy In Gep-nensmentioning
confidence: 99%
“…Objective tumor remissions have been reported in ∼11%, and tumor stabilization in 40–50% [38,39]. One recent prospective French multicenter study with mixed NET reported a progression-free survival (PFS) of 14 months for IFN [40]. Given the increasing number of therapeutic options, IFN is less frequently used for antiproliferative purposes, mainly due to its adverse effects (flu-like symptoms, fatigue, elevation of liver enzymes).…”
Section: Targeting Somatostatin and Dopamine Receptorsmentioning
confidence: 99%